2003
DOI: 10.1037/0893-3200.17.4.521
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adolescent Friends, Romantic Partners, and Siblings in the Emergence of the Adult Antisocial Lifestyle.

Abstract: This study investigated the contribution of social processes in boys' adolescent relationships in 3 key domains-same-sex friends, cross-sex romantic partners, and younger siblings-to continued association with delinquent peers in young adulthood and, therefore, to continuance of an antisocial lifestyle. It was hypothesized that levels of negative interaction and antisocial talk observed during problem-solving discussions would be associated across the 3 domains. The influences of negative interactions and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 55 publications
1
42
0
6
Order By: Relevance
“…This is not surprising, as peer environments foster and support emerging dating dyads (Brown, 1999;Connolly & Goldberg, 1999). Aggressive and delinquent peer involvement facilitate aggression training among adolescents, and processes such as hostile talk or modeling in turn influence romantic interactions, specifically, dating aggression (Capaldi, Dishion, Stoolmiller, & Yoerger, 2001;Dishion, Spracklen, Andrews, & Patterson, 1996;Shortt, Capaldi, Dishion, Bank, & Owen, 2003). Characteristics of the dating relationship are also important to our understanding of the context in which early intimate aggression occurs.…”
mentioning
confidence: 99%
“…This is not surprising, as peer environments foster and support emerging dating dyads (Brown, 1999;Connolly & Goldberg, 1999). Aggressive and delinquent peer involvement facilitate aggression training among adolescents, and processes such as hostile talk or modeling in turn influence romantic interactions, specifically, dating aggression (Capaldi, Dishion, Stoolmiller, & Yoerger, 2001;Dishion, Spracklen, Andrews, & Patterson, 1996;Shortt, Capaldi, Dishion, Bank, & Owen, 2003). Characteristics of the dating relationship are also important to our understanding of the context in which early intimate aggression occurs.…”
mentioning
confidence: 99%
“…The development of risky or delinquent behavior usually begins in the early years by an individual associating with those that are delinquent (Shortt et al, 2003). Without intervention, the negative behavior is likely to continue from one developmental period to another.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent use of retrospective report of family conflict may be particularly subject to bias given the length of time since exposure and involvement in the conflict being reported. With one notable exception [31] the studies also fail to assess conflict between multiple family member dyads. Most previous studies generally include only parental conflict as a predictor (excluding parent-child and sibling conflict) and typically focus on only intimate partner relationships as the outcome (excluding sibling relationships).…”
Section: Consequences Of Parental and Sibling Conflictmentioning
confidence: 99%
“…In a two-year longitudinal study with adolescents, [60] reports that sibling conflict negatively predicted romantic intimacy during late adolescence among girls. In another longitudinal study, this one using the OYS data, [31] found that the OYS boys had 3 times more observed negative interaction with intimate partners and siblings than with friends during late adolescence. The OYS boys had been exposed to high levels of family negativity (e.g., verbal attacks, physical aggression) in middle childhood and had histories of deviancy and antisocial behavior.…”
Section: Consequences Of Parental and Sibling Conflictmentioning
confidence: 99%
See 1 more Smart Citation